Effect of Branch Bending on the Canopy Characteristics and Growth of Peach (Prunus persica (L.) Batsch) - Binbin Zhang; Fengshi Zheng; Wenwen Geng; Hao Du; Yuansong Xiao; Futian Peng (Agronomy, 2023)
A reasonable main branch opening angle can improve the canopy light environment of a tree, change the direction of nutrient transport, and promote the formation of flower buds. In this experiment, 3-year-old ‘Lu Hong 618’ was used as the test material to study the effects of different main branch opening angles (three treatments: 45°, 65°, and 85°) on the canopy light distribution, canopy characteristics, fruit quality, and flower bud quality of ‘Y’-shaped peach trees. The main findings were as follows: the solar energy utilization in the canopy varied greatly between different main branch opening angles, with the best relative light intensity of the canopy at 85°. In addition, the canopy light distribution on photosynthesis was more reasonable at 85°, and the daily variation range of CO2 concentration in the inner canopy was the greatest, which facilitated ventilation and light penetration in the inner canopy. With the increase in the main branch opening angle, the new growth of peach trees and the growth of the main branch trunk were inhibited. A reasonable branch opening angle results in good branch structure and leaf morphology. Leaf stomatal morphology and the soluble sugar and starch contents at different levels of the canopy are influenced by canopy light, and higher levels of canopy light can significantly increase the stomatal size and improve the leaf photosynthetic capacity, SPAD value, and soluble sugar and starch contents. With the increase in the main branch opening angle, C/N tended to increase. In addition, the distribution pattern of fruit quality in the canopy was similar to that of light distribution. In the same fruiting part, the fruit quality was higher at 85° and 45° than at 65° and slightly higher at 85° than at 45°, but the difference was not significant. The effects of different main branch opening angle treatments on the fruit weight, flesh firmness, soluble solids, and titratable acid were more significant. The 85° pulling angle effectively increased the light intensity of the different canopy layers of the peach trees and promoted the accumulation of nutrients. An 85° pulling angle can be used as a more suitable pulling angle for peach tree shaping cultivation.